2013
DOI: 10.1590/s1806-83242013000100018
|View full text |Cite
|
Sign up to set email alerts
|

Concordance between cytopathology and incisional biopsy in the diagnosis of oral squamous cell carcinoma

Abstract: Oral cytopathology is a simple, non-invasive technique that could be used for early detection of oral premalignant and malignant lesions, but the effectiveness of this diagnostic approach remains controversial. The aim of this study was to evaluate the sensitivity, specificity, positive and negative predictive values, and accuracy of cytopathology for diagnosing oral squamous cell carcinoma (OSCC) and the diagnostic concordance between cytopathological and histopathological diagnoses. The study enrolled 172 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…The efficiencies of fine-needle aspiration cytology and brush cytology were defined in the literature [22, 23]. Fontes et al [24] reported that cytopathology was a reliable method with 83.1% sensitivity and 100% specificity for patients who require the diagnosis of suspected squamous cell carcinoma for starting treatment. Thus, when dealing with such pathologic lesions with high misdiagnosis rates, adjunct techniques such as fine-needle aspiration cytology, brush cytology, or blood-urine sample analysis should be considered when appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…The efficiencies of fine-needle aspiration cytology and brush cytology were defined in the literature [22, 23]. Fontes et al [24] reported that cytopathology was a reliable method with 83.1% sensitivity and 100% specificity for patients who require the diagnosis of suspected squamous cell carcinoma for starting treatment. Thus, when dealing with such pathologic lesions with high misdiagnosis rates, adjunct techniques such as fine-needle aspiration cytology, brush cytology, or blood-urine sample analysis should be considered when appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Out of these, exfoliative cytopathology is, particularly, valuable for mass screening of oral carcinoma. Evaluating the quality of cytology as a diagnostic method for OSCC, Fonte et al (2013) have reported that the sensitivity was 83.1%, the specificity was 100%, the positive predictive value (PPV) was 100%, the negative predictive value (NPV) was 49% and the accuracy was 85.5% [56]. Recently, compared with cytopathological and histopathological diagnoses, Hafez et al (2014) have also found that the sensitivity was 93.5%; specificity was 96.2%; PPV was 97.7%; NPV was 89.3% with a diagnostic accuracy of 94.4%.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, patients are often diagnosed in an advanced stage of disease. Diagnosis is late in most cases because patients do not seek treatment or do not have easy access to professionals who can establish the diagnosis [4]. …”
Section: Introductionmentioning
confidence: 99%